Teacher training in Latin America: a parallel between Brazil and Paraguay (Práxis Educativa, 2024)
This study aimed to comprehend the educational structure of Brazil and Paraguay, with a focus on the training of teachers working in literacy classes. To this end, a qualitative documentary research was conducted, in which legal documents that organize the educational system, teacher training, and websites supporting the ongoing training of literacy educators in both countries were analyzed. The theoretical framework for this research was based on the Cultural Studies. Upon completing the investigation, it was understood that the education systems of the nations mentioned guarantee access to education. Therefore, both require as a priority a higher education degree for the teacher to be considered capable of carrying out their duties and, with regard to the continuing training of literacy teachers, this has been taking place via online platforms in programs called Paraguay Aprende, currently active, and Tempo de Aprender, concluded in 2023.Keywords: Education. Brazil and Paraguay. Teacher training.